Flexible data processing system for field survey on domestic animal diversity - Avnish K Bhatia,; Dinesh K Yadav,; Pardeep K Vij, (Journal of Livestock Biodiversity, 2025)
Conservation of domestic animal diversity requires identification and current status of breeds through field surveys in their native tracts followed by data analysis and development of information systems for animal genetic resources. Various animal species possess distinct recording parameters requiring dynamic questionnaire formats. This warrants carefully designed database for development of a flexible computer package for management and analysis of the survey data. This paper describes such a generalized and flexible data processing system.